Surface ruthenated hydrocarbon sensor: statistical optimisation of sensitivity - Chaudhary, V.A; Mulla, I.S; Sainkar, S.R; Mandale, A.B; Vijayamohanan, K (Sensors and actuators. A. Physical., 2000)
A surface functionalised gas sensing material capable of better sensitivity and selectivity is developed by grafting Ru–O linkages on the surface of tin oxide. A statistical technique is employed using a 2 7−3 fractional factorial design to optimise the sensitivity of the ruthenated tin oxide towards hydrocarbons. A systematic evaluation of the mean effects of such a 2 7−3 (i.e., 16) experiments indicates the usefulness of this powerful tool in optimising the sensitivity. Various results of characterisation techniques such as SEM, XPS and EDAX illustrate the reasons for optimum sensitivity in terms of the amount and distribution of Ru species on the surface. A comparison of the results obtained using such a 2 7−3 algorithm against the results of conventional experiments emphasises the importance of the interaction of various experimental parameters during the sensor fabrication.